The self-perceived high level of health quality of Europeans: Spatial analysis of determinants - Elżbieta Antczak; Katarzyna M. Miszczyńska (Journal of Applied Economics, 2020)
The aim of this article is to provide a quantification of the territorially varied relation between socioeconomic factors and share of people perceived their own health as good or very good in European countries in years 2005-2018. The preliminary data analysis shows that, to model health status at the country level, it is necessary to consider the age structure of inhabitants, country specifics and spatial interactions. For the purpose of the research, several causes were identified depending on age category, e.g., crime rate, self-reported unmet needs for medical examination by main reason declared, households with access to the Internet at home, pure alcohol consumption, hospital beds and population by educational attainment level. To increase the explained variability of phenomena and emphasize country-specific differences in the phenomena, geographically weighted regression was applied.
Keywords: 330; Self-perceived health; different age categories; socioeconomic factors; European countries; spatial analysis; geographically weighted regression